Numerical Model of Current Speed in Bojong Salawe Beach, Pangandaran West Java Province - Subiyanto, Subiyanto; Nirwa, Nira na; Yuniarti, Yuniarti; Ihsan, Yudi Nurul; Afrianto, Eddy; Supian, Sudradjat (International Journal of Global Operations Research, 2021)
The purpose of this study was to determine the hydrodynamic conditions at Bojong Salawe beach. The method used in this research is a quantitative method, where numerical data is collected to support the formation of numerical models such as wind, bathymetry, and tide data. The hydrodynamic model will be made using Mike 21 with the Flow Model FM module to determine the current movement pattern based on the data used. In the west monsoon with a maximum instantaneous speed of 0.04 - 0.08 m/s, while in the east monsoon it moves with a maximum instantaneous speed of 0,4 – 0,44 m/s. The dominant direction of current movement tends to the northeast. The results indicate the current speed during the east monsoon is higher than the west monsoon. The difference in the current speed is also influenced by the tide conditions; higher during high tide and lower during low tide. Monsoons also have a role in the current movements, though the effect is not very significant.